Collaborative exercise: analysis of age estimation using a QIAGEN protocol and the PyroMark Q48 platform - Kampmann, Marie-Louise; Fleckhaus, Jan; Børsting, Claus; Jurtíková, Helena; Piters, Alice; Papin, Julien; Gauthier, Quentin; Ghemrawi, Mirna; Doutremepuich, Christian; McCord, Bruce; Schneider, Peter M; Drabek, Jiri; et al. (Forensic sciences research, 2024)
UNLABELLED: Human age estimation from trace samples may give important leads early in a police investigation by contributing to the description of the perpetrator. Several molecular biomarkers are available for the estimation of chronological age, and currently, DNA methylation patterns are the most promising. In this study, a QIAGEN age protocol for age estimation was tested by five forensic genetic laboratories. The assay comprised bisulfite treatment of the extracted DNA, amplification of five CpG loci (in the genes of ELOVL2, C1orf132, TRIM59, KLF14, and FHL2), and sequencing of the amplicons using the PyroMark Q48 platform. Blood samples from 49 individuals with ages ranging from 18 to 64 years as well as negative and methylation controls were analyzed. An existing age estimation model was applied to display a mean absolute deviation of 3.62 years within the reference data set. KEY POINTS: Age determination as an intelligence tool during investigations can be a powerful tool in forensic genetics.In this study, five laboratories ran 49 samples and obtained a mean absolute deviation of 3.62 years.Five markers were analyzed on a PyroMark Q48 platform.